Crystal structure of truncated aspartate transcarbamoylase from Plasmodium falciparum. Issue 7 (1st July 2016) - Lunev, Sergey; Bosch, Soraya S.; Batista, Fernando de Assis; Wrenger, Carsten; Groves, Matthew R.
Abstract : The crystal structure and preliminary structure‐based mutagenesis and activity studies of aspartate transcarbamoylase from P. falciparum are reported. Abstract : The de novo pyrimidine‐biosynthesis pathway of Plasmodium falciparum is a promising target for antimalarial drug discovery. The parasite requires a supply of purines and pyrimidines for growth and proliferation and is unable to take up pyrimidines from the host. Direct (or indirect) inhibition of de novo pyrimidine biosynthesis via dihydroorotate dehydrogenase ( Pf DHODH), the fourth enzyme of the pathway, has already been shown to be lethal to the parasite. In the second step of the plasmodial pyrimidine‐synthesis pathway, aspartate and carbamoyl phosphate are condensed to N ‐carbamoyl‐l ‐aspartate and inorganic phosphate by aspartate transcarbamoylase ( Pf ATC). In this paper, the 2.5 Å resolution crystal structure of Pf ATC is reported. The space group of the Pf ATC crystals was determined to be monoclinic P 21, with unit‐cell parameters a = 87.0, b = 103.8, c = 87.1 Å, α = 90.0, β = 117.7, γ = 90.0°. The presented Pf ATC model shares a high degree of homology with the catalytic domain of Escherichia coli ATC. There is as yet no evidence of the existence of a regulatory domain in Pf ATC. Similarly to E. coli ATC, Pf ATC was modelled as a homotrimer in which each of the three active sites is formed at the oligomeric interface. Each active site comprises residues from two adjacent subunits in the trimer with a high degree of evolutional conservation. Here, the activity loss owing to mutagenesis of the key active‐site residues is also described.